Electrocatalysis enhancement of iron-based catalysts induced by synergy of methanol and oxygen-containing groups. (March 2016) - Yan, Xingxu; Tang, Zhenkun; Xu, Xin; Fang, Fang; Song, Dongsheng; Liu, Jianguo; Lu, Shanfu; Liu, Li-Min; Luo, Jun; Zhu, Jing
Abstract: Direct methanol fuel cells (DMFCs) have been recognized as a promising type of power sources to solve the energy shortage and environmental pollution from fossil energy consumption. However, their commercialization is still hindered by two major problems, the high cost of Pt-based catalysts and the crossover of methanol from anodes to cathodes. In the second problem, the methanol molecules can poison the Pt-based catalysts and lower the cell voltages by reacting with oxygen. Fe-based catalysts containing Fe–N–C active sites are well known as low-cost candidates that are promising to replace the Pt-based. But they cannot prevent the methanol molecules from reacting with oxygen. For the first time, we discovers a new enhancement of the electrocatalysis of Fe–N–C nanofiber catalysts induced by a synergy of methanol and oxygen-containing groups in the catalysts. Its mechanism is revealed by first-principles calculations of density functional theory and then proven experimentally. More significantly, the synergy-induced enhancement (SIE) is further improved experimentally by 40.8 times and reaches 21.60±0.05%. This indicates that the SIE has an enormous upside potential. Moreover, the methanol molecules in the SIE react with not oxygen but epoxy, reducing the harm of the reaction of methanol and oxygen in DMFCs. Further, the SIE has been employed in fuel cells and realized enhancement of current density by 3.0±0.5% in anion-exchange membrane DMFC and by 5.95±0.07% in H2 –O2 anion exchange membrane fuel cell (AEMFC). Therefore, the new SIE can simultaneously solve both of the two problems and thus facilitate the DMFC commercialization for easing the crises of energy and pollution. Graphical abstract: Highlights: Synergy of methanol and oxygen-containing groups in Fe-based catalysts is discovered. The synergy can be practically controlled by the content of oxygen-containing groups. The synergy enhances the current density of oxygen reduction reaction by 21.6%. Fe-based catalysts show a synergy-induced current density 16.8% higher than Pt/C. The synergy works in assembled anion-exchange membrane fuel cell systems.